Analisis Strategi Pemasaran Dalam Upaya Meningkatkan Penjualan Pada Pt. Polar Solusindoutama 2019-2022 - Trimustofa, Ageng; Susmonowati, Trinik (JAMBIS : Jurnal Administrasi Bisnis, 2023)
In an increasingly competitive era of globalization, companies in various industrial sectors are required to develop effective marketing strategies to boost sales volume, maintain market share, and adapt to intense competition. This research focuses on PT. Polar Solusindo Utama, which operates in the photocopier sales, rental, and service industry in Bekasi, Indonesia, during the period of 2018- 2022. The research aims to analyze the marketing strategies implemented by the company and their impact on sales volume. The observation results indicate that PT. Polar Solusindo Utama has faced stiff competition from similar competitors in the region. The company has adopted marketing strategies that encompass the Marketing Mix, including product management, pricing, distribution, and promotion.Over the years, the company experienced fluctuations in the number of customers renting and purchasing their photocopier machines. However, in 2021-2022, a significant increase in the number of customers renting and buying machines occurred. This research also notes the impact of the increased number of customerson the company's revenue, with revenue tending to rise after 2020. Based on thesefindings, the research aims to analyze the marketing strategies employed by PT. Polar Solusindo Utama to explain the fluctuations in sales volume and achieve revenue growth. This research has significant implications for similar companies in the same industry seeking to compete and increase sales volume amid intense competition.